Penerapan teknik swedish massage untuk menurunkan kadar glukosa darah pada penderita diabetes melitus tipe 2 - Wintika, Zsal Zsa Zara; Nugroho, Sri Hananto Ponco; Margono, Margono (Universitas Muhammadiyah Magelang, 2021)
Introduction: Diabetes Mellitus is a chronic disease characterized by blood glucose levels exceeding normal limits. Diabetes Mellitus is a disease whose prevalence continues to increase in the world, both in developed and developing countries. Treatment of Diabetes Mellitus efforts to reduce blood sugar levels can be done by pharmacological and non-pharmacological methods. The pharmacological method can use drugs such as insulin and examples of non-pharmacological therapy to lower blood glucose levels can use Swedish massage because this massage technique can make the body feel relaxed and reduce stress thereby increasing adrenal hormones that stimulate insulin secretion. Objective : This application aims to determine the effectiveness of Swedish Massage to reduce blood glucose levels in Gelangan. Methods: The method used in this application is a case study applied to one patient suffering from type 2 Diabetes Mellitus. By doing the initial method of assessment. Results: There was a decrease in blood glucose levels in the sample with clients with type 2 Diabetes Mellitus at the age of 52 years with an average decrease of 50 mg/dL during the implementation of the Swedish massage twelve times using vaseline. Conclusion: Swedish Massage therapy can reduce blood glucose levels using vaseline. Suggestion: Therefore Swedish Massage can be applied to people with Diabetes Mellitus to help stabilize blood glucose levels. Keywords: Diabetes Mellitus, Swedish Massage, Blood Glucose